DEVELOPMENT OF MSMEs IN THE CREATIVE ECONOMY SECTOR - Aulia, Mahda Rida; Suparno; Lutfia, Annisa (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
The development of UMKM in the creative economy sector faces several challenges, especially the low use of digital technology and the creativity of enterprise for UMKM actors which can hinder the development of enterprises. This research aims to study and understand the role of financial technology, digital marketing, and business creativity on the development of MSMEs in the creative economy sector through a theoretical study approach. Various findings from previous research are used as references and theory development in this research. The qualitative approach method with literature studies was used in the research to obtain a more detailed amount of data and information regarding the factors that influence the development of MSMEs. The main subjects of this research are MSME players located in the DKI Jakarta area. The results of this study indicate that financial technology, digital marketing, and business creativity can help MSME players to develop their businesses so that they can survive and compete in the global market. In addition, this research can also be used as an illustration for MSME actors to know the importance of implementing technology and developing creativity before running a business.